Descanse o seu gatilho: illegal markets’ hegemony and its peace dividends - Oliveira, Bruno Pantaleão de (2023)
In this research I investigate the role of criminal governance in promoting Economic Development. I show that a rational and stable regime of criminal governance provided by a drug-trafficking organization promotes an improvement in the amount of jobs and firms in peripheral regions that are under-served by state services. I find that the presence of criminal governance and the hegemony of a single organized crime group in a large metropolitan area is associated with a reduction in homicides and serious interpersonal violence. My findings suggest that the presence of an hegemonic criminal organization allows for more regular and predictable patterns of governance, and that the organizations’ internal structure plays a key role in shaping the relationship between criminals, the population, and the state.